Human Gastric Mucosal Hydrophobicity Does dot Decrease with Helicobacter Pylori Infection or Chronological Age - Mohammed S Al-Marhoon; Sheila Nunn; Roger W Soames (Canadian Journal of Gastroenterology)
BACKGROUND AND AIMS: Infection with cytotoxin-associated gene A (cagA) Helicobacter pylori is associated with severe gastric diseases. Previous studies in humans have reported a decreased gastric hydrophobicity with H pylori infection. The aim of the present study was to differentiate between the effect of cagA+ and cagA- strains on gastric mucus hydrophobicity.